Assessment of antibiotic prescribing at different hospitals and primary health care facilities - AKICI, AHMET (ELSEVIER, 2013)
In this study, it was aimed to investigate the utilization of antibiotics at various health care facilities. Photocopies of 1250 prescriptions which were containing antibiotics and written out in primary health care facilities (PHCFs), public hospitals (PHs), private hospitals and university hospitals in 10 provinces across Turkey, were evaluated by some drug use indicators. The number of drugs per prescription was 3.23 +/- 0.92 and it was highest in PHCFs (3.34 +/- 0.84), (p < 0.05). The cost per prescription was 33.3 $, being highest in PHs while being lowest in PHCFs (38.6 $ and 28.2 $ respectively). Antibiotic cost per prescription was 16.7 $ and it was also highest and lowest in PHs and PHCFs respectively (p < 0.05). The most commonly prescribed group of antibiotics was beta-lactam antibacterials, penicillins (29.2%) while amoxicillin/clavulanic acid was the most commonly prescribed antibiotic (18.1%). Sixty-one percent of the antibiotics prescribed for acute infections was generics; among facilities being highest in PHCFs (66.5%) and among diagnosis being highest in acute pharyngitis. In general, the duration of antibiotic therapy was approximately 7 days for acute infections. Although much more drugs were prescribed in PHCFs than others, it was found to be in an inverse proportion with both the total cost of prescriptions and the cost of antibiotics. Broad-spectrum antibiotics, beta-lactamase combinations in particular, were considered to be more preferable in all health care facilities is also notable. These results do serve as a guide to achieve the rational use of antibiotics on the basis of health care facilities and indications. (C) 2012 King Saud University. Production and hosting by Elsevier B. V. All rights reserved.
Keywords: Antibiotics; Rational use of medicine; Generic; Prescribing; Health care; RESPIRATORY-TRACT INFECTIONS; GENERAL-PRACTITIONERS; PRESCRIPTION; PHYSICIANS; CONSUMPTION; DIAGNOSIS; HABITS; SURVEILLANCE; METAANALYSIS; MANAGEMENT